Variation of Clinical Features of Covid19 Patients (Bangladesh Journal of Infectious Diseases, 2020)
In December 2019, the novel coronavirus (2019-nCoV) outbreak, began in China, which has now spread many countries around the globe in a form of pandemic, with the number of confirmed cases increasing every day. With a death toll exceeding that of the SARS-CoV outbreak, 2019-nCoV has led to a public health emergency of international concern, putting all health organizations around the world on a high alert. Here, we presented an overview of the currently available information on the clinical presentation and complication of this virus.Bangladesh Journal of Infectious Diseases, April 2020;7(suppl_1):S54-S57